PENGARUH KARAKTERISTIK INDIVIDU, GAYA KEPEMIMPINAN DAN BUDAYA ORGANISASI TERHADAP KOMITMEN ORGANISASI PADA SEKRETARIAT DPRD KABUPATEN BOGOR - Rukmana, Yusuf Maulana; Harini, Sri (Fakultas Ekonomi Universitas Djuanda, 2017)
The aims of this research is to identify the individualâs characteristics, the leadership style and the culture of organization effect on organization commitment at Secretariat DPRD regency Bogor. There are 69 respondents as the sample that were taken. The methods that used in this research are survey method, the form of description and quantitative. Observation, interview and questionnaire are used to collect the data of this research. The test of this research that used are the validity test, reliability test and assumption classic test with likert scale for the double linear regressio and the hypotheses test. The result of this research is all the indicators had valid and reliable as well as fulfill rules and regulations on the assumption classic is simultaneously the individualâs characteristic (X1), the leadership style (X2), and the culture of organization (X3) influential in positive and significant toward organization commitment (Y). In the partial the individualâs characteristic (X1), the leadership style (X2) and the culture of organization (X3) influential in positive and significant toward organization commitment (Y), while leadership style (X3) has not influential in positive and significant toward organization commitment (Y).Keywords: : the individualâs Characteristic, the leadership style, the culture of organization, organization commitment